The Effect Of Green Financing, Corporate Social Responsibility and Cost Efficiency On The Profitability Of Manufacturing Companies In Indonesia: The Role Of Good Corporate Governance As A Moderation Variable - Yunita; Said Musnadi; A Sakir (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study aims to examine the Green Financing, Corporate Social Responsibility (CSR), and Cost Efficiency impact on Profitability, with Good Corporate Governance (GCG) as the moderator. This uses a Linear Regression and Moderated Regression Analysis. The population is the manufacturing companies listed on the IDX for the 2020-2024. Partial testing shows that CSR and cost efficiency affect profitability, while green financing does not have a significant influence. Simultaneous testing indicates that all variables significantly influence profitability. However, the test of variable moderation shows that GCG does not moderate the impact of green financing on profitability, but moderates the impact of CSR and cost efficiency on profitability significantly. This implies that strengthening CSR and achieving operational efficiency are key to driving increased company profitability, as reinforced by GCG.